Hydrothermal Liquefaction of Biomass Using Waste Material as Catalyst: Effect on the Bio-crude Yield and Quality - Benedetta De Caprariis; Martina Damizia; Lingyu Tai; Paolo De Filippis (Chemical Engineering Transactions, 2022)
Hydrothermal liquefaction (HTL) is one of the most promising technologies to produce valuable compounds from biomass and waste. The use of water as solvent makes this process extremely convenient for high moisture feedstock and also environmentally sustainable. However, the obtained product, the bio-crude, is not ready to the end use, its oxygen content is quite high making the oil physically and chemically instable and thus difficult to handle and store. The use of heterogeneous catalysts and hydrogen producers can improve the product quality during the hydrothermal process being also easy to be separated and recirculated. In this work the use of reduced red mud acting as hydrogen producer is tested in the hydrothermal process of oak wood. Red mud is composed mainly by Fe2O3 that was reduced with the char produced by HTL and by a simulated syngas which is obtained from char gasification. The reduced red mud was mixed with the biomass and fed into the HTL batch reactor with variable red mud biomass ratio. The reduction temperature was optimized in order to obtain zero valent Fe able to produce hydrogen reacting with water in HTL conditions. The tests were conducted at 330 °C with a reaction time of 10 min. The obtained bio-crude was characterized with elemental analysis. The results in terms of oil yield and quality were compared with those obtained with pure iron powder showing that red mud can be used successfully as hydrogen producer in HTL process and recycled after its reduction with char or syngas. The use of red mud leads to an increase of the oil yield of 20% with respect to the blank test and looking at the oil composition the hydrogenation effect is evident, the amount of hydrogen increases while the amount of oxygen decreases.